Germinal cord tumors - Dysgerminoma - Chehade, Jorge (1971)
A case of dysgerminoma It comes in a 22-year-old nuligesta. The diagnosis was made during surgery but was confirmed with histopathology. Treatment consisted coforectomía left and postoperative radiation.